Assessing the Synergistic Potential of Ceftazidime–avibactam and Aztreonam against Metallo-beta-lactamase Producing Enterobacterales by Disc Elution and Disc E Strip – Synergy Method - K. M. Aysha Linsy; Anna Rajan Thomas; Nivedha Srinivasan; Sevitha Bhat; Archana Bhat (Annals of African Medicine, 2026)
Abstract Introduction: Emergence of carbapenem-resistant Gram-negative pathogens poses a significant challenge due to limited treatment options and higher mortality rates associated with infections caused by these pathogens. A combination of aztreonam (AT) and ceftazidime/avibactam (CZA-AVI) is an effective combination with synergistic activity against metallo-beta-lactamase (MBL) producing carbapenem resistant Enterobacterales (CRE). This study aimed to compare the disc elution and disc-E strip method for assessing the synergistic effect of aztreonam and ceftazidime/avibactam against MBL-producing CRE, with the potential to inform effective treatment strategies. Methodology: A total of 55 samples were isolated from clinical samples, in which 65.45% Klebsiella pneumoniae and 27.27% Escherichia coli were resistant to the tested carbapenem (meropenem) by the Vitek-2 compact system. Molecular detection of the New Delhi MBL, Verona integron-encoded MBL, or imipenemase gene was performed by conventional multiplex polymerase chain reaction. The synergy between aztreonam (30 μg) and ceftazidime–avibactam (30/20 μg) against MBL-producing CRE was assessed using both the disc elution and the disc-E strip synergy method. Results: Out of the 55 carbapenem-resistant isolates, K. pneumoniae (65.4%) being the most common isolate, and urinary tract and bloodstream infections were the primary sources. Neutropenia was a significant risk factor, and high antibiotic resistance was observed, where 63.4% isolates were extensively drug-resistant, whereas 21% were pan-drug resistant, and 15.4% multidrug-resistant. With increasing awareness among clinicians, CZA-AVI + AT is being used. Comparison between disc elution and disc E-test showed 96.4% concordance. Conclusion: This study highlights the need to evaluate ATM and CAZ/AVI as potential therapeutic alternative for the treatment of infections caused by MBL-producing Enterobacterales . Hence, synergy testing should be incorporated into routine laboratory practises to save time and give appropriate targeted therapy.